Laboratory testing of wood mouse and common vole sensitivity to bromadiolone, sodium selenite, and cellulose - Jokić, Goran; Vukša, Marina; Đedović, Suzana; Kljajić, Petar (Journal of Pest Science, 2014)
Maintaining the numbers of wood mice and common voles at an acceptable economic level, especially during years of massive outbreaks, is a major challenge in plant protection. Efforts to reduce the negative effects of rodenticides on the environment, to improve the integrated pest control system, and to minimize risks for human and animal health require investigation of the potentials of cellulose, as a natural product, and sodium selenite as rodenticides. The present study was conducted to determine the sensitivity of these rodent species to bromadiolone (a.i. 0.005 %), sodium selenite (a.i. 0.1 and 0.05 %), and cellulose (a.i. 45 %) baits. All experiments were done using no-choice and choice feeding trials. A low acceptance of cellulose baits was found in the choice feeding trial, and the time of first deaths indicate that stress and hunger increase the death rate in both species. The taste had a negative impact on the acceptability of baits containing sodium selenite. Low bait acceptance of cellulose and sodium selenite resulted in lower mortality of both species. The acquired results indicate that bromadiolone remains a more effective solution than cellulose and sodium selenite for control of wood mice and common voles.